US Physicians’ Reactions To ACA Implementation, 2012–17 - Riordan, L (Health Aff (Millwood), 2019)
Physicians play a key role in implementing health policy, and U.S. physicians were split in their enthusiasm for the Patient Protection and Affordable Care Act (ACA) soon after its implementation began. We re-administered elements of a prior survey of U.S. physicians to a similar sample to understand how US physician opinions of the ACA may have changed over a crucial five-year implementation period (2012–2017), and compared responses across both surveys. Of the 1,200 physicians to whom we sent a survey, 489 responded in 2017 (RR: 41%). In the summer of 2017, a majority of respondents (60%) believed the ACA improved access to care yet many (43%) acknowledged it reduced affordability of health insurance coverage. More physicians (53%) agreed the ACA “would turn US health care in the right direction” than in 2012 (42%), despite reporting perceived worsening in several practice conditions over that same time period. After adjusting for specialty, political affiliation, practice setting, perceived social responsibility, age, and gender, only political affiliation (Democrat, Republican, Independent) was a significant predictor of support for the ACA in the 2017 results.